Study on the effect of substrates concentration in the production of xylanase from aspergillus niger using palm kernel cake - Abdul Hakim, Rahmad (2006)
Xylanase enzymes have many applications in the paper, food and chemical industries. These enzymes are produced by several microorganisms, mainly from fungal species. In this work a selected fungal called Aspergillus niger was investigated for production of xylanase in solid state fermentation (SSF). The substrates that used in the production of xylanase enzyme from Aspergillus niger were from palm oil waste which called as palm kernel cake. The concentration of the substrates that varied at 1, 3 and 5 g/L was studied in Erlenmeyer flask. The enzyme activity of xylanase was investigated for one week duration that started from the first day until the seventh day of the experiment that based on the activity of xylanase and carboxylmethylcellulase enzyme. Based on the result that obtained through the experiment, it was found that the highest xylanase activity was stated at concentration of 3 g/L on the first day. And for the carboxylmethylcellulase enzyme, the highest of activity was found at the concentration of 3 g/L on the fourth day. By using palm kernel cake as substrates, Aspergillus niger was able to grow and then produce xylanase enzyme